Endoscopic stricturotomy for axis-related gastric outlet obstruction following sleeve gastrectomy - dos Santos, Luana Gabriela; Chinzon, Miriam; Bestetti, Alexandre Moraes; de Moura, Diogo Turiani Hourneaux; de Moura, Eduardo Guimarães Hourneaux (Endoscopy International Open, 2025)
Axis deviation and helical stricture following sleeve gastrectomy may result in functional gastric outlet obstruction, leading to significant patient morbidity. Conventional endoscopic therapies, such as balloon dilation and self-expandable metal stents (SEMS), have demonstrated limited efficacy and are frequently associated with recurrence and complications. This study aimed to assess clinical outcomes of endoscopic stricturotomy as a minimally invasive technique for managing axis-related stenosis after sleeve gastrectomy.This retrospective case series included adult patients (≥ 18 years) who underwent endoscopic stricturotomy for axis-related stenosis at a tertiary academic center from 2019 to 2024. Diagnosis of helical stricture was confirmed via endoscopic and radiologic assessments. Clinical data were obtained through electronic chart review and structured telephone interviews. Symptom severity was evaluated using the Gastroparesis Cardinal Symptom Index (GCSI), and quality of life was assessed using a visual analog scale (VAS). Statistical analysis included the Shapiro-Wilk test and paired t-test or Wilcoxon signed-rank test, with P < 0.05 considered significant.Eight patients (mean age 53 years; 62.5% female) were included, with a mean time of 31.3 months between surgery and stricturotomy. All GCSI domains showed significant symptom improvement. The global GCSI score improved from 35.44 to 21.66 (P = 0.014), and VAS scores increased from 3.0 to 7.75. Complications included two cases of intraoperative pneumoperitoneum and one delayed gastric fistula, all managed non-surgically.Endoscopic stricturotomy is a promising, minimally invasive treatment for axis-related gastric outlet obstruction post-sleeve gastrectomy. Prospective studies are warranted to confirm long-term outcomes.
Keywords: Endoscopy Upper GI Tract; Dilation, injection, stenting; POEM; Endoscopic resection (ESD, EMRc, ...)